Estudo histomorfométrico de implantes craniofaciais em coelhos - Santos Júnior, João Ferreira dos [UNIFESP] (2010)
Purpose: Histomorphometric analysis of craniofacial implants of different shapes and diameters, with machined and porous surfaces, placed in the tibia of rabbits. Method: In this study, 40 craniofacial implants with cylindrical shapes (3.75 and 5.0 mm in diameter) and conical (4.3 mm in diameter) both with 5 mm in length were implanted in the tibia of 8 adult female New Zealand white rabbits. The animals were sacrificed 12 weeks after installation of implants. Bone specimens were prepared for histomorphometric assessment of the bone-to-implant contact and the bone volume formation between implant threads. Results: The overall bone-to-implant contact values (mean and standard deviation) were 73.77 ± 6.25% with porous surface implants and 59.79 ± 8.32% with machined surface implants. Individual group values of bone-to-implant contact were as follows: 5.0 mm porous implant 72.67 ± 7.44%; 5.0 mm machined implant 58.33 ± 7.01%; 4.3 mm porous implant 76.80 ± 5.58%; 4.3 mm machined implant 61.26 ± 9.78%; and 3.75 mm porous implant 71.84 ± 5.24%. Conclusion: There was statistically significant greater bone-to-implant contact values with porous surface implants (p <0.001). There was no statistically significant difference on the bone-to-implant contact between different implant sizes (3.75 mm / 4.3 mm / 5.0 mm) and shapes (cylindrical and conical).